Complement destabilizes cardiomyocyte function in vivo after polymicrobial sepsis and in vitro - Kalbitz, Miriam; Fattahi, Fatemeh; Herron, Todd J.; Grailer, Jamison J.; Jajou, Lawrence; Lu, Hope; Huber-Lang, Markus; Zetoune, Firas S.; Sarma, J. Vidya; Day, Sharlene M.; Russell, Mark W.; Jalife, Jose; et al. (Journal of Immunology, 2016)
There is accumulating evidence during sepsis that cardiomyocyte (CM) homeostasis is compromised, resulting in cardiac dysfunction. An important role for complement in these outcomes is now demonstrated. Addition of C5a to electrically paced CMs caused prolonged elevations of intracellular Ca2+ concentrations during diastole, together with the appearance of spontaneous Ca2+ transients. In polymicrobial sepsis in mice, we found that three key homeostasis-regulating proteins in CMs were reduced: Na+/K+-ATPase, which is vital for effective action potentials in CMs, and two intracellular Ca2+ concentration regulatory proteins, that is, sarcoplasmic/endoplasmic reticulum calcium ATPase 2 and the Na+/Ca2+ exchanger. Sepsis caused reduced mRNA levels and reductions in protein concentrations in CMs for all three proteins. The absence of either C5a receptor mitigated sepsisinduced reductions in the three regulatory proteins. Absence of either C5a receptor (C5aR1 or C5aR2) diminished development of defective systolic and diastolic echocardiographic/Doppler parameters developing in the heart (cardiac output, left ventricular stroke volume, isovolumic relaxation, E9 septal annulus, E/E9 septal annulus, left ventricular diastolic volume). We also found in CMs from septic mice the presence of defective current densities for Ik1, L-type calcium channel, and Na+/Ca2+ exchanger. These defects were accentuated in the copresence of C5a. These data suggest complement-related mechanisms responsible for development of cardiac dysfunction during sepsis.
CRIS-Team Scopus Importer:2020-12-21